2017
DOI: 10.1002/mdc3.12479
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Characteristics of the North‐East Visual Hallucinations Interview in Parkinson's Disease

Abstract: Background Visual Hallucinations (VH) are a common symptom experienced by individuals with Parkinson’s disease (PD); however, a validated measure of VH has yet to be established for this population. The North-East Visual Hallucinations Interview (NEVHI), a promising VH measure, has not been well validated in PD. The aim of this study was to evaluate the convergent and discriminant validity of the NEVHI as well as the proportional identification and characteristics of VH in PD. Methods One hundred seventeen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The MDS Unified Parkinson's Disease Rating Scale -Motor Examination (UPDRS-III), 6 Epworth Sleepiness Scale 7 and Geriatric Depression Scale 8 were administered to patients. The Instrumental Activities of Daily Living (IADL) scale, 9 North-East Visual Hallucinations Inventory, 10 Neuropsychiatric Inventory, 11 Mayo Sleep Questionnaire, 12 Clinician Assessment of Fluctuation 13 and Dementia Cognitive Fluctuation Scale 14 were administered to spouses or close family members acting as informants. The Clinical Dementia Rating scale (CDR) 15 was completed using clinical history and research assessments.…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…The MDS Unified Parkinson's Disease Rating Scale -Motor Examination (UPDRS-III), 6 Epworth Sleepiness Scale 7 and Geriatric Depression Scale 8 were administered to patients. The Instrumental Activities of Daily Living (IADL) scale, 9 North-East Visual Hallucinations Inventory, 10 Neuropsychiatric Inventory, 11 Mayo Sleep Questionnaire, 12 Clinician Assessment of Fluctuation 13 and Dementia Cognitive Fluctuation Scale 14 were administered to spouses or close family members acting as informants. The Clinical Dementia Rating scale (CDR) 15 was completed using clinical history and research assessments.…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…Further, this scale has both informant and patient versions which might allow for enhanced accuracy in terms of frequency. The NEVHI has shown to be a valid and reliable scale with a strong correlation with the MDS-UPDRS hallucination item score, making it a promising scale for trials focusing on VH [ 148 , 149 ] (Additional file 3 : Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…However, further analyses showed that patients in the NEVHI+ had longer non-decision times than NEVHI− and non-decision time correlated positively with higher NEVHI score in this group. As a positive NEVHI score does not necessarily reflect the incidence of visual hallucinations but can be due to other visual problems [ 43 ], we also classified patients on the basis of clinical ratings into those with a history of visual hallucinations and those without. This comparison revealed that individuals with visual hallucinations showed wider boundary separation than those without.…”
Section: Discussionmentioning
confidence: 99%